In Vitro Antioxidant and Antimicrobial Potency of Mimosa pudica of Nepalese Terai Region: Insight into L-Mimosine as an Antibacterial Agent. (7th October 2022) - Mandal, Ashok Kumar; Pandey, Anisha; Sah, Ranjit Kumar; Baral, Adesh; Sah, Phoolgen
Abstract : Aim . The study aimed to evaluate the in vitro antioxidant and antimicrobial potency of Mimosa pudica found wildly in the Terai region of Nepal and assess its physicochemical properties, such as total phenolic content (TPC) and total flavonoid content (TFC). Materials and Methods . The physicochemical properties of ethyl acetate extract of Mimosa pudica (EAMP), such as extractive value, total ash content, loss on drying, and phytochemical screening, were calculated using standard protocols. The TPC was determined by using the Folin–Ciocalteu method taking gallic acid as standard, and TFC was conducted by using the AlCl3 colorimetric method, using a 96-well plate reader. The in vitro antibacterial activity of different concentrations of the extract against four bacterial ATCC strains was determined by the agar well diffusion method in the Mueller Hinton agar (MHA) medium. The in silico molecular docking model was used to ascertain the antibacterial potency of L-mimosine against the selected strains of bacteria used for the in vitro study by calculating the binding affinity towards the protein of bacteria. Results . The preliminary screening of the extract showed the presence of several phytochemicals. The total ash content (7.67%), loss on drying (2.30%), and extractive value (8.966%) were determined by analyzing the crude sample. The total phenolic and flavonoid contents were 418.640 ± 0.018 mg GAE/g (dried extract) and 14.126 ± 0.021 mg QE/g (dried extract), respectively. The extract showed a potent free radical scavenging activity with an IC50 value of 158.95 ± 1.12  µ g/mL. The plant extract also demonstrated the antibacterial activity against both Gram-positive bacteria Staphylococcus aureus (15 mm) and Bacillus cereus (22 mm) and Gram-negative bacteria Escherichia coli (17 mm) and Klebsiella pneumoniae (16 mm) at 200 mg/mL concentration of extract. There was a noteworthy binding affinity of antibiotics with almost all selected bacterial proteins with binding energy against Escherichia coli DNA gyrase subunit B (−5.7 kcal/mol), Staphylococcus aureus DNA gyrase subunit B (−6.1 kcal/mol), Bacillus cereus metallothiol transferase (−5.2 kcal/mol), and Klebsiella pneumoniae beta-lactamase (−6.1 kcal/mole), respectively, with the L-mimosine. Conclusion . The findings of the current study suggest that Mimosa pudica from the Terai region of Nepal is rich in phenolic and flavonoid compounds, has a significant impact on bacterial growth inhibition, and has a notable potential to scavenge free radicals (DPPH). According to the in silico analysis, L-mimosine is a potent antibacterial compound that might be utilised to discover novel antibacterial drugs to combat antibiotic resistance.